Management of Bimaxillary Protrusion A Case Report - Mamun, Mohammad Shamim Al; Hossain, Md Zakir (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
This case report will evaluate the management of bimaxillary protrusion by standard edge wise technique with extraction of premolars. The objective of treatment was to use mild forces and to provide maximum space for the retraction of anterior teeth. The goal of the treatment was to improve facial appearance. The case was successfully managed by extraction of all first Premolars and fixed appliance therapy using standard edge wise mechanics. Post-treatment changes were good and stable Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2